2019
DOI: 10.5812/jjm.98009
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Inhibitory Concentrations of Sodium Houttuyfonate in Combination with Erythromycin Inhibit Biofilm Formation and Expression of IcaA in Staphylococcus epidermidis

Abstract: Background: Staphylococcus epidermidis is an important opportunistic pathogenic bacterium causing infections on implanted medical devices by biofilm formation. Sodium houttuyfonate (SH), which is the active modified compound of Houttuynia cordata is commonly applied for treating chronic bronchitis, purulent skin infections, and respiratory tract infections in China. Objectives: We aimed to investigate the in vitro effects of SH in combination with erythromycin on the production of IcaA and expression of icaA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…SH and SNH are commonly applied for antimicrobial and anti-inflammatory treatment in China. Previous studies by our research group found that SH had antibacterial and antifungal effects in vivo and in vitro, 13,14 and had a promising inhibitory effect on the biofilm formation of Pseudomonas aeruginosa and Candida albicans. 15,16 Both SH and SNH were found to have mild antimicrobial activities with relatively high antibacterial minimum inhibitory concentration values in vitro.…”
mentioning
confidence: 81%
“…SH and SNH are commonly applied for antimicrobial and anti-inflammatory treatment in China. Previous studies by our research group found that SH had antibacterial and antifungal effects in vivo and in vitro, 13,14 and had a promising inhibitory effect on the biofilm formation of Pseudomonas aeruginosa and Candida albicans. 15,16 Both SH and SNH were found to have mild antimicrobial activities with relatively high antibacterial minimum inhibitory concentration values in vitro.…”
mentioning
confidence: 81%